Analisis Tindak Tutur Ilokusi Bertema Vaksin dalam Saluran Youtube Reasearch of Community Mental Health Intiative - Nafikha Putri Arthamevia Maharani; Titis Abhirama Reswara; Yessi Ine Rahmandhani; Adhwa Farah Yosinta; Nadya Fransiska Julianti; Asep Purwo Yudi Utomo; Rossi Galih Kesuma; Ryan Hidayat (Intellektika : Jurnal Ilmiah Mahasiswa, 2025)
Illocutionary speech acts are actions of doing something with a specific purpose and function. Illocutionary speech acts as one of the main aspects of the study of speech. Acts are divided into five types, namely expressive, declarative, assertive, directive, and commissive speech acts. This research focuses its study on illocutionary speech acts in the Research of Community Mental Health Initiative's YouTube channel video playlist entitled "A Playlist About Vaccines". This research aims to analyze five types of illocutionary speech acts in speech delivered through videos on YouTube channels. The research data collection technique uses a qualitative descriptive approach. In this research, we also use the collecting method, listening method, and formal method. Based on the research results, we found several inaccuracies in illocutionary speech acts, namely, expressive, declarative, assertive, directive, and commissive speech acts. The benefit of this research is to develop science and knowledge about illusionary speech acts. For the public, this research is useful in increasing their general knowledge regarding the use of speech acts. With this research, it is hoped that it can become reference material for other writers who will conduct similar research. The data taken in this research is an analysis of illusionary speech acts in the Vaccine video on the YouTube Channel Research of Community Mental Health Initiative.